Micro milling of polymeric micro injected specimens with randomly oriented carbon nanotube fillers. (27th February 2020) - Pagano, Claudia; Attanasio, Aldo; Rebaioli, Lara; Ceretti, Elisabetta; Fassi, Irene
The interest in the application of carbon nanotube (CNT) composites is recently increasing in several industrial sectors. The main reason for this growing attention is the reinforcing effect of the CNTs. However, the composite use is limited by technological issues concerning the manufacturing processes when small features are required. A multistage process chain could exploit the advantages of suitable processes to enhance the control of the filler orientation. This paper investigates the feasibility of milling micro features on micro injected specimens of POM/CNT and LCP/CNT composites. Design of experiment is used to study a suitable experimental design to investigate the influence of the material and the process parameters on the machinability and the feature geometry. POM-based composites showed a better machinability and allowed a fabrication of more accurate features, while LCP showed high cutting forces and the presence of diffused burrs, preventing the fabrication of very small features.